Soft \(n\)-Normed Linear Spaces: Generalizations and Extensions from Soft Normed Spaces - Reddy, B. Surender; Vijayabalaji, S.; Punniyamoorthy, K.; Rao, A. V. Raghavendra (Communications in Mathematics and Applications, 2024)
This article presents the notion of soft 2-normed linear space (NDLS) and extends it to soft \(n\)-NDLS, providing a versatile framework beyond traditional soft NDLS and \(n\)-normed spaces (NDS). Established results in soft NDLS are adapted to soft \(n\)-NDLS, bolstered by practical examples.
Keywords: Soft sets; Soft linear spaces; Soft NDLS; Soft \(n\)-NDLS